2021
DOI: 10.1080/15398285.2020.1858258
|View full text |Cite
|
Sign up to set email alerts
|

The Literacy Demand of Cancer & COVID-19 Consumer Health Information

Abstract: The Internet is widely used for accessing COVID-19 information and while abundant, it is frequently complex, inconsistent, and contradictory. This "misinfodemic" has repeatedly revealed low health literacy to be an underestimated public health problem. This study evaluated whether this holds true for information about COVID-19 and cancer on commonly visited websites. "Coronavirus and cancer" and "COVID-19 and cancer" were entered in Google Canada and the first 10 results were evaluated for readability, underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The plethora of contradictory information available on the pandemic makes it challenging for patients to evaluate sources and subsequently assess risk accurately. 35 Participants cited difficulty with assessing the quality of entire media (eg, television stations and journal articles) because the quality within each type of media could vary considerably. Use of social media, however, indicated greater worry among participants, and this may point to the availability of misinformation online.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plethora of contradictory information available on the pandemic makes it challenging for patients to evaluate sources and subsequently assess risk accurately. 35 Participants cited difficulty with assessing the quality of entire media (eg, television stations and journal articles) because the quality within each type of media could vary considerably. Use of social media, however, indicated greater worry among participants, and this may point to the availability of misinformation online.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis indicates the importance of language proficiency, education, and information sources in shaping patient attitudes toward the pandemic. The plethora of contradictory information available on the pandemic makes it challenging for patients to evaluate sources and subsequently assess risk accurately 35 . Participants cited difficulty with assessing the quality of entire media (eg, television stations and journal articles) because the quality within each type of media could vary considerably.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of responses among those participants may point to confusion on their part. Scholars have pointed to the existence of a “misinfodemic” following the emergence of COVID-19, which has been compounded by the fact that factual information is inaccessible for much of the public [ 30 ]. The information that is available may be oversimplified and severely lacking in nuance [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this medical jargon is obscure to laymen and may require patients to ask for more details to be sure that they understand their condition and treatment plans ( Josh, 2017 ). A recent study ( Papadakos et al, 2021 ) showed the effect of health literacy on the accuracy of the information laymen are seeking related to coronavirus (COVID-19) and cancer. The study concluded that much of the cancer and COVID-19 information available does match with patients’ health literacy because much of the present information has been written using professional terminology which is hard for laymen to understand.…”
Section: Introductionmentioning
confidence: 99%